2007
DOI: 10.1007/s10439-007-9275-0
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Simulation of Red Blood Cell Deformation and Lateral Migration in Microvessels

Abstract: A theoretical method is used to simulate the motion and deformation of mammalian red blood cells (RBCs) in microvessels, based on knowledge of the mechanical characteristics of RBCs. Each RBC is represented as a set of interconnected viscoelastic elements in two dimensions. The motion and deformation of the cell and the motion of the surrounding fluid are computed using a finite-element numerical method. Simulations of RBC motion in simple shear flow of a high-viscosity fluid show "tank-treading'' motion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
132
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(142 citation statements)
references
References 26 publications
10
132
0
Order By: Relevance
“…Unlike RBCs, for vesicles we can vary their intrinsic characteristic parameters (e.g., size, degree of deflation, and nature of internal fluid). Despite the simplicity of their structure, vesicles have exhibited many features observed for red blood cells: equilibrium shapes [21], tank-treading motion [3,22], lateral migration [15,23,24], or slipperlike shapes [25,26]. Capsules (a model system incorporating shear elasticity) have also revealed some common features with vesicles [27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike RBCs, for vesicles we can vary their intrinsic characteristic parameters (e.g., size, degree of deflation, and nature of internal fluid). Despite the simplicity of their structure, vesicles have exhibited many features observed for red blood cells: equilibrium shapes [21], tank-treading motion [3,22], lateral migration [15,23,24], or slipperlike shapes [25,26]. Capsules (a model system incorporating shear elasticity) have also revealed some common features with vesicles [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…We use large systems (in lattice units) because of the higher resolution required to extract the results shown below. Previous works done in 2D dealing with vesicles (also for red blood cells) have demonstrated that the dynamics in the third dimension is not relevant, even in confined geometries [23,24,29]. Vesicle dynamics under shear has been extensively studied in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Beside the above mentioned partitioning mechanisms, basically relying on a flow rate unbalance, several studies have investigated the possibility of exploiting particle deformability for their separation in bifurcations [17][18][19]. The capability of sorting particles based on their mechanical properties is of primary importance in medicine, since cell deformability is a clinical indicator of a wide range of diseases, e.g., malaria [20] and leukemia [21].…”
mentioning
confidence: 99%
“…In the last decade, Secomb et al [17,18] Elastic beads were studied with finite element approach by Trofa et al [26], hinting at the possibility of their sorting based on their elastic moduli in a T-shaped microchannel.…”
mentioning
confidence: 99%
“…In recent years, particle methods were used to model rbc behaviour in microvessels [5,6,7], since the motion, deformation and the fluid structure interacion of rbcs are easily modelled. In reality, the motion and deformation of the rbcs are highly three dimensional, as they exhibit three dimensional deformations in microvessels [8]. Therefore, simplified two dimensional models are not enough to capture the actual behaviour of rbcs in microvessels.…”
mentioning
confidence: 99%